Diagnosis of diabetic polyneuropathy in type 2 diabetes mellitus: focus on changes in peripheral nerves according to ultrasonic research method - Zoya V. Karaseva; Alexander S. Ametov; Victoria G. Saltykova; Evgeniya Yu. Pashkova; Larisa V. Kuznetsova; Ksenia G. Yudina (Digital Diagnostics, 2024)
BACKGROUND: Diabetic polyneuropathy remains a significant and urgent problem in the context of diabetes mellitus, affecting more than a quarter of patients with type 2 diabetes mellitus.